Glomangiopericytoma - A Rare Sino-Nasal Tumour - Shravanthi Mantra Prithviraj; Shyam Sudhakar Sudarsan; Dinesh Ram Ravi; Sarah Grace Priyadarshini (Dr. Annil Mahajan, 2024)
Haemangiopericytoma, an uncommon vascular tumor originating from perivascular cells, encompasses a sinonasal variant known as glomangiopericytoma (GPC). A 75-year-old female presented with complaints of recurrent episodes of bleeding from the left nasal cavity for 8 months, along with a history of recurrent episodes of headaches and left nasal obstruction for 6 months. DNE was done and showed a polypoidal vascular mass filling the left nasal cavity. CECT PNS was done, showing signs of sinonasal malignancy. Biopsy showed features of low-grade spindle cell carcinoma. Debulking of the tumour followed by FESS with medial maxillectomy was done successfully, with currently no signs of recurrence.